Recent Dune Migration Along the Coastal Plain of Canoa Quebrada, Ceará State, Northeast Brazil - Pedrosa, Adriana Albuquerque; Claudino-Sales, Vanda; Cavalcante, IItabaraci Nazareno; Carvalho, Alexandre Medeiros (Journal of Environmental Geography, 2019)
In the coastal area of Ceará State, northeast Brazil, there are large mobile dunefields, including barchans, barchanoid dunes and sandsheets. The migration rate of these dunes, as measured by several studies, varies between 32 m/y and 9 m/y. This paper analyzes the migration of the dunes in Canoa Quebrada Beach, located in the eastern coast of Ceará State, using remote sensing of aerial photos and satellite imagery from 1988 to 2013 (25 years). The resulting data indicate an average migration rate varying from 1.8 m/y to 9.3 m/y. This is the lowest rate of migration measured for large and undeveloped mobile dunes in Ceará State. The analysis indicates that the element responsible for this low rate is the low wind speed. However, the installation of wind power turbines in the area – which demanded the fixation of part of the dunes to prevent the equipment from being buried and from aeolian erosion – might be another reason for the decreasing dune migration. The dune migration decrease may increase the sedimentary deficit in the coastline downdrift of Canoa Quebrada Beach.